Exploring the Impact of a country's economic state on consumer associations with cult brands in a third world, South African context - Doubell, Jeana (The IIE, 2017)
This study made use a triangulation research approach including quantitative, qualitative and action research to generate reliable and valid insight into South African consumer associations with three cult brands – Apple, Harley Davidson and Mini Cooper. Taken from a third world country perspective, this study explored the relationship between different economic groups within Cape Town, South Africa act as a starting point to better understand the dynamic that a country’s economic state impacts on the success of cult brands. This study may act as the starting point for future studies conducted on marketing strategies for cult brand or brands moving towards cult status.
Keywords: Brands; Branding; Marketing; Marketing Strategies; Cult Brands